Optimization of Vortex Tube Design and Performance for Cooling Milling Process - Sifa, Agus; Endramawan, Tito; Safi'i, M. Iksan; Wardika (International Journal of Integrated Engineering, 2023)
The manufacturing process is required to improve cleanliness and reduce environmental pollution and the exploration of natural resources is limited. One of the manufacturing processes is machining, especially the milling process. The phenomenon during the milling process friction occurs when the workpiece is cut by the milling tool, the effect friction between tool and workpiece occurs temperature rise. To reduce the temperature rise of the milling tool during the workpiece cutting process, an effective and efficient alternative cooling is needed through the use of vortex tubes. The research method was carried out using the Computational Fluid Dynamic (CFD) approach and experiments with the use of inlet pressure = 1-5 Bar, and the parameters of variations in valve shape, number of nozzles, and pipe lengths. The overall results of the CFD and experiment of parameters in inlet pressure on the number of nozzles, valve shapes, and tube lengths, have an impact on the increasing inlet pressure, the higher the thermodynamic characteristics that occur in the vortex tube, but there is a loss of outlet pressure in each parameter. The geometry of the vortex tube selected is the number of nozzles 6, valve fillet shape, and tube length of 50 mm, vortex tube can be used for cooling the milling tool with the addition of a flexible hose at a distance of 5 cm from the tooltip.